2022
DOI: 10.48550/arxiv.2202.06817
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

CATs++: Boosting Cost Aggregation with Convolutions and Transformers

Abstract: Cost aggregation is a highly important process in image matching tasks, which aims to disambiguate the noisy matching scores. Existing methods generally tackle this by hand-crafted or CNN-based methods, which either lack robustness to severe deformations or inherit the limitation of CNNs that fail to discriminate incorrect matches due to limited receptive fields and inadaptability. In this paper, we introduce Cost Aggregation with Transformers (CATs) to tackle this by exploring global consensus among initial c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
25
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(25 citation statements)
references
References 72 publications
0
25
0
Order By: Relevance
“…7. We note the resolution which the method is evaluated, since [9,78] observe that the resolution of images affect the PCK performance, and the resolution of which the method outputs the correspondence field. It is shown that NeMF achieves competitive performance or even attains state-of-the-art performance for several alpha thresholds.…”
Section: Matching Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…7. We note the resolution which the method is evaluated, since [9,78] observe that the resolution of images affect the PCK performance, and the resolution of which the method outputs the correspondence field. It is shown that NeMF achieves competitive performance or even attains state-of-the-art performance for several alpha thresholds.…”
Section: Matching Resultsmentioning
confidence: 99%
“…CHM [47] extends the PHM by employing high-dimensional convolutional kernels to aggregate 6D correlation maps. CATs [8] and its extension [9] use transformers [79,12] to explore global consensus from correlation maps thanks to transformers' ability to consider long-range interactions. All these works exploit rich semantics present at high-level features for robust matching across semantically similar images.…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…We believe that PCF-Net points out a novel direction for solving correspondence problems: learning reliable and geometric-invariant probabilistic coordinate representations. Future research directions include further optimization through cost aggregation [64] and graph matching [65].…”
Section: Discussionmentioning
confidence: 99%
“…Due to these unconstrained settings, it should handle the additional challenges of large intra-class variations in appearance and background clutter. Recent deep learning-based matching models (Min et al 2019a;Liu et al 2020;Li et al 2020a;Li et al 2021;Zhao et al 2021;Min et al 2020;Cho et al 2021;Cho, Hong, and Kim 2022), following data-driven approach, were generally trained in a supervised fashion based on datasets (Ham et al ‡ Work done while at NAVER AI Lab. Correspondence to Dongyoon Han: dongyoon.han@navercorp.com.…”
Section: Introductionmentioning
confidence: 99%